Behavioral and cytogenetic analysis of the cacophony courtship song mutant and interacting genetic variants in Drosophila melanogaster. - Kulkarni, S.J.; Hall, J.C. (Genetics, 1987)
The courtship song of a Drosophila melanogaster male consists of tone pulses interspersed with humming sounds. An X chromosomal mutation, cacophony (cac), causes the production of polycyclic pulses readily distinguishable from those in wild type, which are mono- or bicyclic. Yet, courtship hums and flight wing beats are normal in this mutant, suggesting a specific role of the cac gene in the neural program underlying one particular feature of the fly's wing vibrations. A precise cytogenetic localization of cac is presented; this was obtained by uncovering the song abnormality with deletions that are missing all or the distal part of region 11A; the flies tested were diplo-X adults that had been turned into males by the transformer mutation. Duplications including distal 11A covered cac. The possibility of behavioral specificity for cac's effects was examined by screening a variety of sexual and nonsexual behaviors; these experiments included tests of flies in which the mutation was uncovered by a small deletion. We conclude that cac causes only a limited array of well-defined defects: longer and louder tone pulses in the song and depressed locomotor activity. Further complementation tests involving cac and other closely linked genetic variants--the night-blind-A (nbA) visual mutation, l(1)L13 lethal mutations, and a series of X chromosomal breakpoints--suggested complex interactions among these factors: the breakpoints uncover all three types of mutations; cac and nbA appear to be alleles of l(1)L13, whereas the two behavioral mutations complement each other.